Defending Aviation Cyber-Physical Systems from DDOS Attack Using NARX Model - Alsulami, Abdulaziz A.; Zein-Sabatto, Saleh (Advances in Artificial Intelligence and Applied Cognitive Computing, 2021)
Recently, the aviation industries showed interest in transferring their aircraft models to cyber-physical system (CPS)-based models. However, and as it is well known, CPS introduces security threats to the physical components of the system. Distributed Denial-of-Service (DDOS) attack is one of the significant security threats to the availability of the communication network, due to making the network resources unavailable. In the presence of DDOS attack, servers are overwhelmed with so many requests which increase the network traffic that causes packet loss. Therefore, this paper proposes an approach to defending the communication network system in the aviation cyber-physical system (ACPS) from a DDOS attack using a nonlinear autoregressive exogenous (NARX) model. NARX network is used to predict packets that were dropped due to a DDOS attack. The real-time simulation results showed that the network system in ACPS was successfully defended from the DDOS attack because the ACPS maintained the expected normal performance during the DDOS attack.